The Analysis of Netspeak Used on Instagram - Marissa Swanda Tupamahu; Lulu Jola Uktolseja; Sherly Gaspersz (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Analyzing netspeak used on Instagram involves examining the linguistic and communicative features that are common on the platform. Instagram is a highly visual social media platform, and while it primarily revolves around sharing images and videos, text-based communication in the form of captions, comments, and direct messages plays a crucial role in enhancing the user experience and conveying meaning. This study attempts to discover the use of written communication features on researchers Instagram explore bar. The qualitative method is applied and the data was gathered through observation and documentation and then analyzed in terms of graphology, typography, grammar, vocabulary, and discourse features. This research found some distinctive graphic features such as emojis, correct spelling, lack of punctuation, hashtags, and turn-taking that presents unique coherence and chronological order. The result highlights the complex aspects available in the data, including informality and anomalies that frequently break the rules of conventional language enforced by internet users. Furthermore, the discovery demonstrates that written language development on Netspeak is a method for overcoming expressive obstacles in Instagram communication.